2014
DOI: 10.4236/ajcc.2014.33025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Vulnerability of Food Availability to Climate Change in Hai District, Kilimanjaro Region, Tanzania

Abstract: Climate change has a large effect on agriculture sector and, consequently, on the food available for residents of Hai District and other regions of Tanzania. Based on four decades of climate data, this study assessed the impacts of climate change and its potential vulnerability on food availability in Hai District, Kilimanjaro region. The results from this study suggest an association between food crop production and variation in climate (temperature and rainfall) in Hai District. Considering the aspect of rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Hence the most recurrent sources or causes of vulnerability identified by farmers were poverty (98.3%), inadequate rainfall (85.8%), limited weather information (55.8%), and biased land tenure system (55%) while the least recurrent causes of vulnerability perceived by farmers were limited access to credit facilities (20.8%) and soil infertility (15.8%). Similar studies conducted by Tabi et al (2012) in the Volta Region of Ghana; Lema et al (2014) in the Hai District, Kilimanjaro Region, Tanzania; Rurinda (2014); Rurinda et al (2014) in the smallholder farming systems of Zimbabwe; Harvey et al (2014) in Madagascar and the FAO (2016) showed that there are several causes of smallholder farmers' vulnerability and small-scale farmers themselves always cite a combination of factors responsible for their vulnerability in the face of climate variability and change.…”
Section: Farmer Identified Causes or Sources Of Vulnerabilitymentioning
confidence: 61%
“…Hence the most recurrent sources or causes of vulnerability identified by farmers were poverty (98.3%), inadequate rainfall (85.8%), limited weather information (55.8%), and biased land tenure system (55%) while the least recurrent causes of vulnerability perceived by farmers were limited access to credit facilities (20.8%) and soil infertility (15.8%). Similar studies conducted by Tabi et al (2012) in the Volta Region of Ghana; Lema et al (2014) in the Hai District, Kilimanjaro Region, Tanzania; Rurinda (2014); Rurinda et al (2014) in the smallholder farming systems of Zimbabwe; Harvey et al (2014) in Madagascar and the FAO (2016) showed that there are several causes of smallholder farmers' vulnerability and small-scale farmers themselves always cite a combination of factors responsible for their vulnerability in the face of climate variability and change.…”
Section: Farmer Identified Causes or Sources Of Vulnerabilitymentioning
confidence: 61%
“…Different studies conducted to investigate the impact of climate change on crop production in Tanzania have reported mixed relationship between climate change and variability on crop production. Lema et al (2014) reported the existence of positive relationship between rainfall and maize and beans; and negative relationship between temperature and maize and beans. Haji (2013) identified a positive correlation between rainfalls, mean minimum temperature and maize yield, but maximum temperature showed a negative relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The basic causes describe the economic, social, environmental and cultural context as well as education and technology, which are mainly at the regional, national and international levels [27] and [28]. Furthermore, the underlying causes, which are generally at the family level [27], are divided into three, namely 1) adequate access to food, including the availability of food production, both individually and in groups and sufficient costs to obtain the food [29] and [30]; 2) adequate care, namely parenting patterns [27]; and 3) health services and a healthy environment, including access to health facilities, such as hospitals [31], clean water and access to sanitation/waste disposal [25], [27] and [31]. The last is direct causes which include food intake and health or disease status [27] and [28].…”
Section: Discussionmentioning
confidence: 99%